1998
DOI: 10.1177/0739456x9801800203
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Equity in Central Cities: Socioeconomic Dimensions and Planning Strategies

Abstract: This study presents the case of a neighborhood in South Phoenix, Arizona, where latent feelings of inequity in the community were heightened by a serious contamination incident. The incident amplified perceptions of environmental risk and reinforced perceptions of distributional, procedural, and process inequities. Housing prices within the affected area continue to reflect a risk-induced discount when compared to those in adjacent and similar neighborhoods. The property value diminution in the affected area h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Sunbelt cities like Phoenix have received little attention in the literature, although they frequently exhibit a myriad of pollution, contamination, and land-degradation problems as a consequence of rapid, poorly planned growth and weak environmental regulation. Studies of Western US cities consistently demonstrate that technological hazards and other locally unwanted land uses are inequitably distributed by race and class (for example, Boer et al, 1997;Bolin et al, 2000;Boone and Modarres, 1999;Clarke and Gerlak, 1998;Davis, 1998;Laituri and Kirby, 1994;Pastor et al, 2001;Pijawka et al, 1998;Pulido, 2000;Pulido et al, 1996;Sadd et al, 1999;Szasz and Meuser, 2000). This suggests that late-developing, highly suburbanized cities of the Western US Sunbelt frequently exhibit environmental injustices, although they generally do not have significant large-scale`smokestack industries' typical of cities like Chicago, Detroit, and Pittsburgh.…”
Section: Sunbelt Urbanizationmentioning
confidence: 99%
“…Sunbelt cities like Phoenix have received little attention in the literature, although they frequently exhibit a myriad of pollution, contamination, and land-degradation problems as a consequence of rapid, poorly planned growth and weak environmental regulation. Studies of Western US cities consistently demonstrate that technological hazards and other locally unwanted land uses are inequitably distributed by race and class (for example, Boer et al, 1997;Bolin et al, 2000;Boone and Modarres, 1999;Clarke and Gerlak, 1998;Davis, 1998;Laituri and Kirby, 1994;Pastor et al, 2001;Pijawka et al, 1998;Pulido, 2000;Pulido et al, 1996;Sadd et al, 1999;Szasz and Meuser, 2000). This suggests that late-developing, highly suburbanized cities of the Western US Sunbelt frequently exhibit environmental injustices, although they generally do not have significant large-scale`smokestack industries' typical of cities like Chicago, Detroit, and Pittsburgh.…”
Section: Sunbelt Urbanizationmentioning
confidence: 99%
“…Also, content analysis of media coverage was used by past research to determine sources of amplification of risk [2], to define stages of post-disaster recovery [40], and to investigate the amplification and the attenuation of the issues that emerged subsequent to a technological toxic event in Central Phoenix [13].…”
Section: Methodsmentioning
confidence: 99%
“…Within this context, Rogers [21] observed that public concern and activism over a chemical plant fire ignited by lightning -"an act of God", was relatively lower than the controversy and citizen political activism over a proposed hazardous waste facility -a technological hazard. Furthermore, the public often identifies a perpetrator with a technological hazard, often resulting in an adversarial relationship between the "perpetrator" and the victims of the hazard [13,22]. Such adversarial relationships often lead to heightened emotional response and sustained political activity, and public demand for governmental regulatory action.…”
Section: Disasters As Focusing Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…List et al (1991) followed another path, analyzing the trade-offs between the response time, risk, cost and equity of the danger when locating response equipments. Other authors, such as Pijawka et al (1998) state that an effective risks reduction in the transportation of dangerous substances is improving the level of the community's knowledge and training. In this sense, the aim centers in the evaluation of the "vulnerability" (or degree of threat of a hazardous waste/hazmat) of a population and it is the ability to mitigate the consequences of possible incidents.…”
Section: Literature Reviewmentioning
confidence: 98%